On Determination of Pollution in Urban Junction, Caused by Vehicles - Hajderi, Asllan; Gjevori, Shkelqim (European Journal of Sustainable Development, 2013)
In this study, given the determination of the pollution quantity from vehicles in an urbanjunction in order to reduce the pollution level and fuel. The pollution caused by vehicles,it is taken based on production years within the EC directives. Types of vehiclescirculating are determined based on vehicles state, divided by production years and thetype of engine.For urban junction with roundabout "Zogu Zi", they are performed measurements ofvehicles number, that move in an hour, describing way with slowly and relevant time. Forthis junction it is calculated vehicle speed at the junction and pollution quantity isconverted to g/min and then it is determined the pollution quantity per hour for existingstate of vehicles divided into 5 groups, according to pollution level. For practicalapplication, only vehicles manufactured after 2000 in circulation, it results that can beachieved a pollution reduction at the junction up to 3 times. To realize this, it is proposedthe removal of customs duty for vehicles manufactured after 2001 and establishment ofadditional environmental tax, proportional to the pollution degree for vehicles incirculation.